The Iran-Iraq War - Willett, Edward (New York, NY The Rosen Publishing Group, INC, 2004)
Examines the history behind the longest war of the twentieth century, which raged between Iran and Iraq in the 1980s, and looks at its ongoing ramifications.
The stage is set -- Iraq attacks -- Iran strikes back -- The tanker war and the war of the cities -- The tide turns.
Includes bibliography references and Index
10 - 12 years
Keywords: Iran-Iraq War -- Juvenile literature -- 1980-1988